Temporal Trends in Geographic Distribution of PICUs in the United States 2001–2023 - Eleanor Gradidge; Abigail Shih; Kaeli Samson; Christina Cifra; Robin Klein; Adrienne G. Randolph (Pediatric Critical Care Medicine, 2026)
Objectives: To identify and describe changes in the geographic distribution of PICUs across the United States from 2001 to 2023. Design: Cross-sectional study over three time points using geographic methods to calculate distances to the nearest PICU, change in distances to the nearest PICU over time, and changes in rates of access by census tract. Setting: U.S. PICUs. Participants: None. Interventions: None. Measurements and Main Results: The primary outcome was the distance from a given U.S. census tract center to the nearest PICU. Distances were grouped by U.S. census regions and divisions. Most PICUs were located in urban areas. The median distance from census tract centers to the nearest PICU was 12.5 miles (interquartile range [IQR], 4.5–37.1 miles), 12.8 miles (IQR, 4.9–36.2 miles), and 13.3 miles (IQR, 5.2–36.0 miles) for 2001, 2016, and 2023, respectively. In all years, PICUs were localized to a single city in Arkansas, Nebraska, and Oregon, and there were no PICUs in Wyoming. In 2023, the median distance to a PICU from the nearest census tract was 7.4 miles in the Middle Atlantic division (NJ, NY, and PA) and 30.1 miles in the East South Central division (AL, KY, MS, and TN). The distance to a PICU was shorter for coastal regions compared with large areas of the Mountain and Pacific divisions. Conclusions: The geographic distribution of PICUs across the U.S. varied over time, with PICU beds remaining concentrated in urban areas, whereas rural areas were farther from the nearest PICU. This results in inequitable access for critically ill children, particularly in the western U.S. Understanding the variation in geographic access to PICUs is an essential step toward ensuring equitable access to life-saving care for all children.